Factors Related To Nurses’ Hospital Management And Work Engagement In The Radiology Department - Ismail , Moamen Abdelfadil; Alhopish, Aisha Abdullah; ALROBAIE, SAMEER HELAL; Alenezy, Houda Bander; alrefai, Bashayer saleam; Alhabeshi, Fatimah Abdullah; ALhobashi, Manal abdullah; qari, Afnan fadulallah; Alghamdi , Khulud Ahmed (Journal of Ecohumanism, 2024)
Background: Work engagement is critical for nurse performance and well-being, particularly in specialized areas such as radiology, where occupational hazards like radiation exposure and high-stress environments are prevalent. Despite the increasing demand for radiological nursing care, many nurses express reluctance to work in radiology due to health concerns and limited support systems. Methods: This study was conducted among nurses working in radiology departments of cancer care hospitals . Data were collected using a demographic questionnaire, the Utrecht Work Engagement Scale (UWES), and a survey assessing perceptions of radiation safety. Descriptive and multiple regression analyses were performed to identify factors influencing work engagement. Results: Out of 200 participants, the mean UWES score was 54.3 (SD = 18.4), reflecting moderate work engagement. Absorption scored slightly higher than vigor and dedication. Key predictors of engagement included nurses’ preference for radiology assignments and the availability of radiation exposure consultation services. While nurses reported confidence in workplace safety measures, gaps in consultation services and education about long-term risks were noted. Demographic factors, such as age and professional position, also played a role in engagement levels. Conclusion: Work engagement among radiology nurses is influenced by a complex interplay of individual preferences and organizational factors. Enhancing consultation services, providing targeted training, and implementing specialized support programs are essential strategies for fostering engagement in high-stress environments. Further research is needed to develop tailored interventions to address these challenges and improve outcomes in radiology nursing.